1997
DOI: 10.1093/ndt/12.6.1116
|View full text |Cite
|
Sign up to set email alerts
|

D-Penicillamine reduces renal injury in the remnant model of chronic renal failure in the rat

Abstract: These findings demonstrate that DPC reduces renal injury in the remnant kidney, and raise the possibility of a therapeutic role for DPC in the treatment of patients with chronic renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Early reports of a correlation between urinary hydrogen ion content and protein excretion in human subjects [lo] have been confirmed in rats, which develop proteinuria when made acidotic for short periods by dietary ammonium chloride (NH,Cl) [l 13. It was originally proposed that this proteinuria resulted from increased protein filtration at the glomerulus, but recent data from this laboratory have shown that short-term acidosis causes a significant increase in urinary lysozyme and N-acetylglucosaminidase, while excretion of immunoglobulin G remains relatively unchanged [12]. This profile suggests tubular, rather than glomerular, injury and is consistent with immunohistochemical studies of kidneys from rats given dietary hydrochloric acid supplements for 14 days.…”
Section: Introductionsupporting
confidence: 69%
“…Early reports of a correlation between urinary hydrogen ion content and protein excretion in human subjects [lo] have been confirmed in rats, which develop proteinuria when made acidotic for short periods by dietary ammonium chloride (NH,Cl) [l 13. It was originally proposed that this proteinuria resulted from increased protein filtration at the glomerulus, but recent data from this laboratory have shown that short-term acidosis causes a significant increase in urinary lysozyme and N-acetylglucosaminidase, while excretion of immunoglobulin G remains relatively unchanged [12]. This profile suggests tubular, rather than glomerular, injury and is consistent with immunohistochemical studies of kidneys from rats given dietary hydrochloric acid supplements for 14 days.…”
Section: Introductionsupporting
confidence: 69%
“…262 Other studies have used cytokines such as relaxin, 187 hepatocytegrowthfactor, 263,264 and bone morphogenetic protein 7. 202 Antifibrotic agents [265][266][267] have also produced encouraging results. Dietary Modification.…”
Section: Early Nephrology Referralmentioning
confidence: 99%
“…In the commonly used 5/6 nephrectomy model, the remnant kidney usually exhibits early compensatory hypertrophy, glomerular perfusion, a high filtration rate, and hyperpressure; these developments are followed by glomerular sclerosis, capillary loop collapse, progressive mesangial expansion, tubular interstitial damage, and, ultimately, progressive renal failure [22]. Also, rats from which two-thirds of kidney tissue has been removed have been used to investigate residual renal destruction [24]. However, this model is not widely employed.…”
mentioning
confidence: 99%